Istanbul gezi rehberi - Belge, Murat, 1943- (Istanbul : Türkiye Ekonomik ve Toplumsal Tarih Vakfi, 1999)
Istanbul, travel and descriptions.
This book is in Turkish.
Keywords: Istanbul (Turkey) -- Guidebooks